TSP-1-1223 A/G Polymorphism as a Potential Predictor of the Recurrence Risk of Bladder Cancer in a Chinese Population - Li, Pengchao; Yang, Xiao; Yang, Xuejian; Qin, Chao; Cao, Qiang; Zhang, Zhengdong; Wang, Meilin; Cai, Hongzhou; Gu, Jinbao; Tao, Jun; Gu, Min; Lu, Qiang; et al. (International journal of genomics, 2013)
Backgrounds. TSP-1 is a glycoprotein that functions in the biology of bladder cancer. We investigated the relationship between the distribution of TSP-1-1223 A/G polymorphism (rs2169830) and the clinical characteristics of bladder cancer. Materials and Methods. TaqMan assay was performed to determine the genotype of 609 cases and 670 control subjects in a Chinese population. Logistic regression was used to assess the association between the polymorphism and the risk of bladder cancer. Quantitative real-time polymerase chain reaction was performed to determine TSP-1 mRNA expression. Survival curves were generated using the Kaplan-Meier method. Results. No significant differences were detected in the genotype frequencies of healthy control subjects and patients with bladder cancer. By contrast, the time until the first recurrence differed significantly between genotypes (P=0.017). The expression of TSP-1 mRNA in bladder cancer tissues was lower in patients with an AG genotype than in those with an AA genotype. The lowest expression was observed in patients with a GG genotype. Conclusions. In conclusion, TSP-1-1223 A/G polymorphism may contribute to the recurrence of bladder cancer in Chinese population.